2018
DOI: 10.1093/humrep/dey078
|View full text |Cite
|
Sign up to set email alerts
|

The relation of age at menarche with age at natural menopause: a population study of 336 788 women in Norway

Abstract: STUDY QUESTIONIs age at menarche associated with age at menopause or with duration of the reproductive period (interval between menarche and menopause)?SUMMARY ANSWERThe association of age at menarche with age at menopause was weak and non-linear, and the duration of the reproductive period decreased by increasing age at menarche.WHAT IS KNOWN ALREADYIt remains uncertain whether age at menarche is associated with age at menopause. Some studies report that women with early menarche also have early menopause. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 57 publications
7
42
0
4
Order By: Relevance
“…This may be because menarche is the first life event that occurs just after one decade of life, whereas menopause occurs after four or five decades of life-time enough for the two events to become completely dissociated (Sievert, 2006). A similar kind of result is also evident in other studies (Bjelland, Hofvind, Byberg, & Eskild, 2018;Van Noord et al, 1997;Yasui et al, 2012). Age at menopause and age at menarche have been associated with the health of the women (Day et al, 2015;Dossus et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…This may be because menarche is the first life event that occurs just after one decade of life, whereas menopause occurs after four or five decades of life-time enough for the two events to become completely dissociated (Sievert, 2006). A similar kind of result is also evident in other studies (Bjelland, Hofvind, Byberg, & Eskild, 2018;Van Noord et al, 1997;Yasui et al, 2012). Age at menopause and age at menarche have been associated with the health of the women (Day et al, 2015;Dossus et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Our research showed that weight may be related to the age of menopause, which is consistent with the report by other papers [21][22][23][24]. The age of menarche was signi cantly related to the age of menopause, similar to previous research in Norwegian women [25]. People with earlier menarche age have earlier menopause; those with later menarche age have relatively late menopause age.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it may be that the insignificant relationship is due to a lack of clarity within the data. Although, the results do suggest that women who have smoked and have a lower BMI enter menopause earlier, which is in line with previous research (Ayatollahi et al, 2005;Bjelland et al, 2018;Gold et al, 2001Gold et al, , 2000McKnight et al, 2011;Nagel et al, 2005;Özdemir & Çöl, 2004;Parazzini, 2007;Sapre & Thakur, 2014;Tao et al, 2015;Wang et al, 2018), suggesting that the data are, to an extent, capturing significant behavioral and lifestyle influences on menopause timing even if women were only estimating when they experienced menopause. We also observe that women who have more children report an earlier ANM, and on average women who live away from their natal group have higher parity.…”
Section: Discussionsupporting
confidence: 90%
“…Covariates were held constant in each analyses and selected based on existing literature on the demographic correlates of menopause symptoms and timing, and also based on the data we had available. These included parity (Li et al, ; Mishra et al, ; Parazzini, ; Wang et al, ), whether the woman was financially secure over the past year (as a measure of socioeconomic position/financial stress; Lawlor, Ebrahim, & Smith, ; Schoenaker, Jackson, Rowlands, & Mishra, ), body mass index (BMI; Ahuja, ; Li et al, ; Maru, Verma, Verma, & Shrimal, ; Parazzini, ; Sapre & Thakur, ; Tao et al, ; Wang et al, ; Zhu et al, ), and smoking habits (Ayatollahi, Ghaem, & Ayatollahi, ; Bjelland, Hofvind, Byberg, & Eskild, ; Gold et al, , ; McKnight et al, ; Nagel, Altenburg, Nieters, Boffetta, & Linseisen, ; Özdemir & Çöl, ; Parazzini, ; Sapre & Thakur, ; Tao et al, ; Wang et al, ). In addition, age was included in the model when looking at symptom duration and symptom severity, and menopause status when looking at symptom severity, to control for the possibility that retrospective accounts of menopause may differ to current reporting.…”
Section: Methodsmentioning
confidence: 99%